Spatio-temporal variability in hydro-chemical characteristics of coastal waters of Salimpur, Chittagong along the Bay of Bengal - Talukder, Avijit; Mallick, Debbrota; Hasin, Tasnuba; Anka, Ishrat Zahan; Hasan, Md Mehedi (Journal of Fisheries, 2016)
Diverse seasonal characteristics of hydro-chemical parameters in the coastal zone are significantly related to aquaculture development. In this paper, general water quality condition derived from laboratory analysis from the coastal waters of Salimpur, Chittagong is presented. Samples were collected from onshore and offshore site of two adjacent coastal locations named as North Salimpur (experimental location) and South Kattoli (control) during a monsoon and a dry season spanning 2013-14. The spatio-temporal variability of studied parameters were found as air temperature 26.5-32.5 ˚C, water temperature 23-33 °C, pH 7.1-7.9, DO 4.29-7.11 mg/L, BOD 1.10-3.25 mg/L, salinity 1.6-21 ppt, EC 3.40-35.68 mS/cm, TDS 2.02-21.99 g/L, TSS 0.62-2.76 g/L, transparency 4.5-14 cm, precipitation 64-1992 mm, NO2-N 1.94-2.58 µg/L, PO4-P 0.45-1.84 µg/L, SiO3-Si 130.46-956.31 µg/L during investigation period. Average values of physicochemical parameters were found to be in compliance with standard guidelines. The ship breaking activities near experimental location possess negative impacts on local geomorphology, freshwater inputs, precipitation and aquatic environment as well. Moreover, wind driven forces, tidal action, wave characteristics and changes in monsoon pattern regulate the coastal processes. This research suggests the importance of regular monitoring to assess present status of water quality and future prospect of aquaculture in the Chittagong coastal zone.